Early oxidative shifts in mouse skeletal muscle morphology with high‐fat diet consumption do not lead to functional improvements. Issue 9 (17th September 2014) - Thomas, Melissa M.; Trajcevski, Karin E.; Coleman, Samantha K.; Jiang, Maggie; Di Michele, Joseph; O'Neill, Hayley M.; Lally, James S.; Steinberg, Gregory R.; Hawke, Thomas J.
Abstract Short‐term consumption of a high‐fat diet (HFD) can result in an oxidative shift in adult skeletal muscle. However, the impact of HFD on young, growing muscle is largely unknown. Thus, 4‐week‐old mice were randomly divided into sedentary HFD (60% kcal from fat), sedentary standard chow (control), or exercise‐trained standard chow. Tibialis anterior (TA) and soleus muscles were examined for morphological and functional changes after 3 weeks. HFD consumption increased body and epididymal fat mass and induced whole body glucose intolerance versus control mice. Compared to controls, both HFD and exercise‐trained TA muscles displayed a greater proportion of oxidative fibers and a trend for an increased succinate dehydrogenase (SDH) content. The soleus also displayed an oxidative shift with increased SDH content in HFD mice. Despite the aforementioned changes, palmitate oxidation rates were not different between groups. To determine if the adaptive changes with HFD manifest as a functional improvement, all groups performed pre‐ and postexperiment aerobic exercise tests. As expected, exercise‐trained mice improved significantly compared to controls, however, no improvement was observed in HFD mice. Interestingly, capillary density was lower in HFD muscles; a finding which may contribute to the lack of functional differences seen with HFD despite the oxidative shift in skeletal muscle morphology. Taken together, our data demonstrate that young, growing muscle exhibits early oxidative shifts in response to a HFD, but these changes do not translate to functional benefits in palmitate oxidation, muscle fatigue resistance, or whole body exercise capacity.